LIPUS regulates the progression of knee osteoarthritis in mice through primary cilia-mediated TRPV4 channels - Sha Wu; Haiqi Zhou; Huixian Ling; Yuyan Sun; Ziyu Luo; ThaiNamanh Ngo; Yuanyuan Fu; Wen Wang; Ying Kong (Apoptosis, 2024)
Osteoarthritis (OA) is a common disease in middle-aged and elderly people. An imbalance in calcium ion homeostasis will contribute to chondrocyte apoptosis and ultimately lead to the progression of OA. Transient receptor potential channel 4 (TRPV4) is involved in the regulation of intracellular calcium homeostasis. TRPV4 is expressed in primary cilia, which can sense mechanical stimuli from outside the cell, and its abnormal expression is closely related to the development of OA. Low-intensity pulsed ultrasound (LIPUS) can alleviate chondrocyte apoptosis while the exact mechanism is unclear. In this project, with the aim of revealing the mechanism of action of LIPUS, we proposed to use OA chondrocytes and animal models, LIPUS intervention, inhibition of primary cilia, use TRPV4 inhibitors or TRPV4 agonist, and use Immunofluorescence (IF), Immunohistochemistry (IHC), Western Blot (WB), Quantitative Real-time PCR (QP) to detect the expression of cartilage synthetic matrix and endoplasmic reticulum stress markers. The results revealed that LIPUS altered primary cilia expression, promoted synthetic matrix metabolism in articular chondrocytes and was associated with primary cilia. In addition, LIPUS exerted a active effect on OA by activating TRPV4, inducing calcium inward flow, and facilitating the entry of NF-κB into the nucleus to regulate synthetic matrix gene transcription. Inhibition of TRPV4 altered primary cilia expression in response to LIPUS stimulation, and knockdown of primary cilia similarly inhibited TRPV4 function. These results suggest that LIPUS mediates TRPV4 channels through primary cilia to regulate the process of knee osteoarthritis in mice.